E-Government Innovation: Digital Identity Services in Cirebon Regency - Nabila Putri Salsabila; Rd. Mahendra Haryo Bharoto (Publikasi Indonesia, 2026)
The development of information technology has encouraged the government to innovate public services through the implementation of e-government, one of which is the Digital Population Identity (Identitas Kependudukan Digital/IKD) by the Cirebon Regency Population and Civil Registration Office (Dinas Kependudukan dan Pencatatan Sipil). IKD was implemented as an effort to transform digital-based population administration services to be more practical, fast, and efficient. However, the implementation of IKD still faces several obstacles, such as low public understanding of digital technology, inadequate socialization, limited internet access, and technical difficulties during the activation and use of the application. Some people also still prefer physical documents, as these are considered easier to use. This study aims to analyze the implementation of IKD in public services in Cirebon Regency, identify the obstacles faced, and determine the role of IKD in improving the quality of public services. The study employed a qualitative method using interview and document analysis techniques. The research informants were community members who use the IKD application. The results showed that IKD makes it easier for the public to access population administration services digitally. IKD is considered practical and efficient and is able to reduce the need for people to come directly to service offices. Although there were obstacles in the initial stages of use, assistance from officers helped the community understand how to use the IKD application.